2016
DOI: 10.1589/jpts.28.2830
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sacral sitting in a wheelchair on the distribution of contact pressure on the buttocks and back and shear force on the ischial region

Abstract: [Purpose] The purpose of this study was to investigate the influence of sacral sitting in a wheelchair on contact pressure on the buttocks and back, and shear force on the ischial region. [Subjects and Methods] Twenty-six healthy adults assumed two postures while seated in a wheelchair: a basic sitting posture, and sacral sitting with the pelvis tilted posteriorly and the ischium slid forward by 5 cm relative to its position in the basic sitting posture. The inclination angle of the sagittal pelvic line, conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Furthermore, researchers have reported that when a shear force is high, vascular occlusion occurs at half the pressure of a low shear force, resulting in the viewpoint that this shear force is a more important factor [ 11 ]. This suggests that the effect of shear forces on the obstruction of blood flow may be a significant factor in pressure ulcers, and efforts have been made to determine the effect of shear forces acting on the buttocks of wheelchair users [ 12 , 13 , 14 , 15 ]. However, one problem in the way of research progress is the difficulty in measuring shear force in wheelchair users, compared with pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, researchers have reported that when a shear force is high, vascular occlusion occurs at half the pressure of a low shear force, resulting in the viewpoint that this shear force is a more important factor [ 11 ]. This suggests that the effect of shear forces on the obstruction of blood flow may be a significant factor in pressure ulcers, and efforts have been made to determine the effect of shear forces acting on the buttocks of wheelchair users [ 12 , 13 , 14 , 15 ]. However, one problem in the way of research progress is the difficulty in measuring shear force in wheelchair users, compared with pressure.…”
Section: Introductionmentioning
confidence: 99%
“…After this discovery, several research groups tried to evaluate the shearing force applied to the buttocks placed on a wheelchair. (6)(7)(8) For example, Kobara et al used a kind of force plate to measure the total shear force applied to the entire seating surface of a wheelchair. (7) Recently, we developed a shear force sensor to evaluate the local shear force in different postures, and found that regardless of posture, a backward-directed shearing force occurred below the ischial tuberosity in seated positions.…”
Section: Introductionmentioning
confidence: 99%